Comparison of Aerodynamic Effects Promoted by Mechanical and Fluidic Miniflaps on an Airfoil NACA 4412 - Casper, M.; Scholz, P.; Colman, J.; Leo, J. Marañón Di; Delnero, S.; Camocardi, M. (IntechOpen, 2012)
None